Stigma Sosial dan Rekonstruksi Identitas Diri pada Pengidap Skizofrenia: Kajian Fenomenologis: Social Stigma and Self-Identity Reconstruction in Schizophrenia Sufferers: A Phenomenological Study - Gregorius Andrea Mustikaningrat , Gregorius Andrea Mustikaningrat; Siswanto, Siswanto; Margaretha sih setija utami, Margaretha sih setija utami (Information Technology and Science (ITScience), 2026)
This study aims to analyse how social construction shapes public perceptions of people with schizophrenia and how social stigma influences the formation and reconstruction of their self-identity. Schizophrenia has been wrongly perceived as a dangerous and incurable condition, thus giving rise to a strong social stigma. To understand this phenomenon, this study used a qualitative approach with an Interpretative Phenomenological Analysis (IPA) design on three participants diagnosed with schizophrenia and undergoing therapy at a rehabilitation institution in Semarang City. Data were collected through in-depth interviews and were analysed thematically to explore the meaning of the participants' subjective experiences. The results revealed four main themes, namely: (1) the social construction of schizophrenia through the process of labelling and stereotyping; (2) internalisation of stigma that influences self-identity; (3) the role of social support in the process of identity reconstruction; and (4) clinical and social implications towards a holistic recovery approach. These findings reveal that social support plays a significant role in reducing the negative impact of self-stigma and helping individuals rebuild a positive identity. This study emphasises the importance of a multidimensional approach in the recovery of people with schizophrenia that combines medical, social, and psychological aspects.